Risk factors for premature ventricular contractions in young and healthy adults. Issue 9 (21st October 2016) - von Rotz, Mirco; Aeschbacher, Stefanie; Bossard, Matthias; Schoen, Tobias; Blum, Steffen; Schneider, Susanna; Estis, Joel; Todd, John; Risch, Martin; Risch, Lorenz; Conen, David
Abstract : Background: Premature ventricular contractions (PVCs) are associated with an increased risk of morbidity and mortality. Therefore, it was aimed to assess risk factors for the frequency of PVCs in young and healthy adults. Methods: Our population-based study included 2048 healthy adults from the general population aged 25–41 years. PVC frequency was determined by 24-hour Holter ECG. We performed multivariable regression analysis using stepwise backward selection to identify factors independently associated with PVC frequency. Results: Median age was 37 years, 953 (46.5%) were male. At least one PVC during the 24-hour monitoring period was observed in 69% of participants. Median number of detected PVCs was 2, the 95th percentile was 193. In multivariable regression analyses, we found 17 significant risk factors for PVC frequency. Low educational status (risk ratio (RR) 3.33; 95% CI 1.98 to 5.60), body height>median (1.58, 95% CI 1.11 to 2.24) and increasing levels of waist:hip ratio (2.15, 95% CI 1.77 to 2.61), N-terminal pro brain natriuretic peptide (1.52, 95% CI 1.30 to 1.76) and Sokolow-Lyon Index (1.38, 95% CI 1.15 to 1.66) (all p≤0.01) were associated with a higher PVC frequency. Physical activity (RR fourth vs first quartile 0.51, 95% CI 0.34 to 0.76) and increasing levels of haemoglobin (0.58, 95% CI 0.47 to 0.70) and glucagon-like peptide-1 (0.72, 95% CI 0.64 to 0.82) (all p<0.001) were related to a lower PVC frequency. Conclusions: PVC occurrence is common even in healthy low-risk individuals, and its frequency is associated with several covariates mainly related to cardiovascular risk factors, markers of cardiac structure and function and socioeconomic status.